2016
DOI: 10.1007/s12253-015-0032-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lymphocyte to Monocyte Ratio, Microvessel Density and HiGH CD44 Tumor Cell Expression in Non Hodgkin Lymphomas

Abstract: Prognostic significance of immune microenvironment has been emphasized using the most advanced analysis, with consecutive attempts to reveal prognostic impact of this findings. The aim of this study was to compare and define prognostic significance of clinical parameters, microvessel density (MVD) in tumour tissue and expression of CD44s as adhesive molecule on tumour cells in diffuse large B cell lymphoma-DLBCL, primary central nervous system DLBCL-CNS DLBCL and follicular lymphoma-FL. A total of 202 histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 46 publications
(74 reference statements)
2
10
1
2
Order By: Relevance
“…We have previously published data to show that low lymphocyte count is significantly associated with adverse outcomes [ 15 ]. Similar findings and other parameters of high monocytes and decreased lymphocyte/monocyte ratio have also been found to be associated with poor prognosis [ 16 20 ]. Low levels of CD4+ T cells appear to be an independent predictor of inferior survival [ 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…We have previously published data to show that low lymphocyte count is significantly associated with adverse outcomes [ 15 ]. Similar findings and other parameters of high monocytes and decreased lymphocyte/monocyte ratio have also been found to be associated with poor prognosis [ 16 20 ]. Low levels of CD4+ T cells appear to be an independent predictor of inferior survival [ 21 ].…”
Section: Introductionsupporting
confidence: 78%
“…The MVD and VEGF levels in non‐Hodgkin's lymphoma (NHL) patients are associated with histological grade, clinical stage, and outcomes . Data on angiogenesis in HL patients are limited to a few reports on VEGF expression and MVD .…”
Section: Discussionmentioning
confidence: 99%
“…32 The MVD and VEGF levels in non-Hodgkin's lymphoma (NHL) patients are associated with histological grade, clinical stage, and outcomes. 15,[33][34][35][36] Data on angiogenesis in HL patients are limited to a few reports on VEGF expression and MVD. [37][38][39] In our present study, we found that high MVD was associated with poorer clinical outcomes, but a higher VEGF expression level was not.…”
Section: Discussionmentioning
confidence: 99%
“…25 A number of studies have revealed a positive relationship between CD44 expression and microvessel density (MVD), which is a characteristic of angiogenesis, in human tumor samples. 35,36,38,[54][55][56][57][58][59][60] A parallel increase in CD44 expression and high MVD has been observed in a variety of cancer types, such as infiltrating ductal carcinoma, 38 renal cell carcinoma, 56 and oral squamous cell carcinoma 35 (summarized in Table 1). In the oral orthotopic carcinogenesis mouse model, CD44 expression becomes upregulated in perivascular area along with excessive blood vessel formation during cancer progression.…”
Section: Cd44 In Tumor Angiogenesismentioning
confidence: 99%